Pharmacogenetic differences between warfarin, acenocoumarol and phenprocoumon - Beinema, Maarten; Brouwers, Jacobus R B J; Schalekamp, Tom; Wilffert, Bob (Thrombosis and haemostasis, 2008)
Coumarin oral anticoagulant drugs have proven to be effective for the prevention of thromboembolic events. World-wide, warfarin is the most prescribed drug. In Europe, acenocoumarol and phenprocoumon are also administered. Yet it has been proven that variant alleles of the VKORC1 and CYP2C9 genotypes influence the pharmacokinetics and pharmacodynamics of these drugs. The combination of these two variant genotypes is a major cause of the inter-individual differences in coumarin anticoagulant drug dosage. Individuals who test positive for both variant genotypes are at increased risk of major bleeding. The impact of the CYP2C9 and VKORC1 genotype is most significant during the initial period of coumarin anticoagulant therapy. The effect of VKORC1 allelic variants is relatively similar for all three VKAs. The CYP2C9 polymorphism is associated with delayed stabilisation for coumarin anticoagulants. The effects of CYP2C9 polymorphisms on the pharmacokinetics and anticoagulant response are least pronounced in the case of phenprocoumon. In the long term, patients using phenprocoumon have more often international normalised ratio (INR) values in the therapeutic range, requiring fewer monitoring visits. This leads us to conclude that in the absence of pharmacogenetic testing, phenprocoumon seems preferable for use in long-term therapeutic anticoagulation. Pharmacogenetic testing before initiating coumarin oral anticoagulants may add to the safety of all coumarin anticoagulants especially in the elderly receiving multiple drugs.